User Interaction Interface Design and Innovation Based on Artificial Intelligence Technology - Li, Xuanyi; Zheng, Haotian; Chen, Jianlong; Zong, Yanqi; Yu, Liqiang (Journal of Theory and Practice of Engineering Science, 2024)
At a time when artificial intelligence is widely used in all walks of life, the way users interact with the digital world also needs to incorporate intelligent elements to reduce the cost of connectivity. This cost can be quantified through "experience metrics", which reveal the problems users encounter when using the interface (UI), and make targeted optimization. With AI, deep learning and prediction of user behavior can be achieved to anticipate and address potential barriers to use in UI design. This will not only improve the user experience, but also promote the development of UI design in a more user-friendly and intelligent direction. Through accurate analysis of experience indicators and combined with AI technology to optimize design, the gap between users and the digital world can be greatly reduced, making digital products more suitable for user needs and achieving seamless interactive experience.